THE IMPACT OF ICTS ON CORE SECTORS OF THE NIGERIAN ECONOMY (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
Information and Communication Technology (ICT) has taken the center stage in almost every aspect of human endeavor. ICT help companies to improve the efficiency and effectiveness of services offered to customers, and thus enhances business processes, managerial decision making, and workgroup collaborations, thus strengthening their competitive positions in rapidly changing and emerging economies. This paper considers the impacts and trends of ICTs on core sectors of the Nigerian economy. Three core industry sectors of the Nigerian economy were examined namely: Banking Industry, Oil and Gas Industry, and Agricultural Industry in order to examine the level of impact ICTs have on the overall Nigerian economy.